INTONATION ERRORS OF THAI STUDENTS IN SPEAKING ENGLISH - Reskyani Reskyani (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2024)
This research aims to determine how the intonation errors of Thai students in speaking English especially in rising and falling intonation. This research used a quantitative method of analysis. The type of this research is classroom action research (CAR). Meanwhile, CAR research is to find or apply a method or approach to learning in the class that is appropriate to the problem encountered. Furthermore, the researcher chose the fourth grade of Prathom Miftahuddeen (Banpleetai) School Nathawee, Songkhla, Thailand totaling 46 students. However, the researcher only took 20 students especially the 4/2 classes the sample of this research. The data in this research were obtained through Pre-Test, Cycle 1, Cycle 2. The data from the mean of the Pre-test, Cycle 1, and Cycle 2 using the SPSS 21 application. The research showed that students’ grades increase after being given the treatment using speech rising and falling intonation about the traditional food of Thailand (Tom Kha Kai). These are shown by the mean scores of the Pre-test (67,95% or 68%), the mean of Cycle 1 (83,15%), and the mean of Cycle 2 (95%). So the skill of the students in rising and falling intonation in the fourth grade of Prathom Miftahuddeen (Banpleetai) School Nathawee, Songkhla, Thailand has been successful and effective.